Polystyrene Trap / Muhammad Irfan Noor Hisham … [et al.] - Noor Hisham, Muhammad Irfan; Idris, Nor Amiro; Sagadevan, Prathibvaran; Mohd. Nazri, Noorul Syahirah Aimi; Noor Hasnan, Amiera Narissa (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Polystyrene is garbage with no expiry date! In Malaysia, polystyrene is widely used although it is known that it contains the monomer, styrene which can cause cancer. Among the reasons it is so popular are because the price is very cheap and it is disposable. We observed that the great numbers of polystyrene waste disposed at designated landfill or in the open. This causes environmental pollution and harm to human life and environment. We make this assumption, if the residual polystyrene can be removed and stored, in any form, then the effect on the environment is minimized. This gives us the idea to produce Styrene Trap. Styrene Trap is a composite material which combines concrete and crushed polystyrene. Polystyrene trapped in cement concrete so it stripping out of sight, stuck together in the concrete. It is lighter than ordinary concrete so it is portable. It can be used as a non-heavy load concrete especially for ornamental garden.